2019
DOI: 10.1096/fj.201802597rr
|View full text |Cite
|
Sign up to set email alerts
|

JNK1 regulates RANKL‐induced osteoclastogenesis via activation of a novel Bcl‐2‐Beclin1‐autophagy pathway

Abstract: JNK1 plays an important role in osteoclastogenesis in response to the osteoclastogenic cytokine receptor activator for nuclear factor‐κB ligand (RANKL). JNK1 is widely accepted as an autophagy regulator under stress conditions. However, the role of JNK1‐mediated autophagy in osteoclastogenesis remains largely unknown. In the current study, our data showed that JNK1 inhibition by a pharmacological inhibitor or RNA interference significantly reduced the autophagic response induced by RANKL in osteoclast precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 58 publications
(92 reference statements)
4
41
0
Order By: Relevance
“…In addition, Annexin V–FITC/PI staining results showed that in the presence or absence of RANKL, the addition of 17β‐estradiol (5 nmol/L) promoted the apoptosis of OCPs (Figure ), which was similar to the previous results 19,20 . Furthermore, OCP apoptosis increased with RANKL treatment (Figure ), which was also consistent with previous research results showing that RANKL promoted OCP apoptosis at the beginning of the precursor stage 52,53 …”
Section: Resultssupporting
confidence: 91%
“…In addition, Annexin V–FITC/PI staining results showed that in the presence or absence of RANKL, the addition of 17β‐estradiol (5 nmol/L) promoted the apoptosis of OCPs (Figure ), which was similar to the previous results 19,20 . Furthermore, OCP apoptosis increased with RANKL treatment (Figure ), which was also consistent with previous research results showing that RANKL promoted OCP apoptosis at the beginning of the precursor stage 52,53 …”
Section: Resultssupporting
confidence: 91%
“…In addition to the integrity of autophagy to the bioactivity of the host cells, novel data highlighted the interaction and interplay of the autophagy signaling pathway with another signaling cascade reciprocally [11]. Scientific literature demonstrated that autophagy functions in the developmental and maturation of B lymphocytes, adipocytes, osteoblasts, keratinocytes and erythrocytes [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Dissociation of the Beclin 1-Bcl-2 complex stimulates autophagy in response to conditions of nutrient deprivation and other cellular stresses [24]. Previous reports have demonstrated that Bcl-2 is phosphorylated at multiple sites, including threonine 69, serine 70 and serine 87, by JNK, causing the dissociation of Beclin 1 and the induction of autophagy [25]. Because ROP17 contains conserved ATP-binding residues and catalytic triads that are essential for S/T kinases, similar to JNK [26], we sought to determine whether ROP17 can phosphorylate Bcl-2 and then liberate Beclin 1 to trigger autophagy.…”
Section: Tgrop17 Phosphorylates Bcl-2 To Induce the Dissociation Of Tmentioning
confidence: 99%